(untitled) (Journal of science and technology exploration, 2026)
Taking the period from 4000 BC to the Renaissance as its temporal span, this paper systematically compares the differences in the development paths of large-scale architectural technologies between the Eastern architectural system represented by the Sinic cultural sphere and the Western architectural system represented by the circum-Mediterranean cultural sphere. The study finds that both Eastern and Western architectural technologies originated in rammed earth and simple stone-brick structures in their early stages. However, due to differences in geographical environment, climatic conditions, and social demands, they subsequently evolved along distinctly different trajectories. Western architecture followed a technological path of “stone and brick–column orders–arches–domes–pendentives,” placing emphasis on breakthroughs in spatial span and vertical height. In contrast, Eastern architecture followed an evolutionary route of “rammed earth–timber frame–dougong brackets–column reduction method,” stressing the refinement of the timber structural system and structural equilibrium. This divergence not only reflects the diversity of technological choices, but also embodies the unique understandings of the relationship between humanity and nature in different civilizations. This paper argues that there is no single superior path in the development of architectural technology; rather, each path represents the crystallization of wisdom through which different civilizations adapted to their own environmental conditions.